The German inflation trauma: Weimar's policy lessons between persistence and reconstruction - David Barkhausen; Sebastian Teupe (Humboldt University Berlin, 2023)
The notion of a nation-specific inflation trauma among the German population is ubiquitous in the public debate in Germany and beyond. Because of its experience with hyperinflation in 1923, the German population fears rising prices and favors stability-oriented monetary as well as fiscal policy. It is less clear, however, whether this contemporary understanding of the German inflation trauma is as old as its historical point of reference. The majority of the literature presumes that such a traumatic disposition has persisted since 1923 and has been transposed intergenerationally (persistence thesis). Others, however, point to an ex-ante reconstruction of past experiences (reconstruction thesis). By employing an interdisciplinary approach of methodological triangulation drawing on both methods of history and political sciences, we provide new insights on the question of origin. Specifically, we examine the remembrance of hyperinflation in personal memoirs and the German Bundestag in regard to the monetary and fiscal policy lessons connected to memories of 1923. Doing so, we find support for the logic of reconstruction. We show that the hyperinflation was not remembered unambiguously, and that memories were not immediately linked to specific policy lessons. Only from the 1980s onwards, a process of discursive alignment occurred that mirrors the contemporary understanding of the inflation trauma. By providing this insight, our paper allows to better understand the historical origins of today's popular memory and its political uses.
urn:nbn:de:kobv:11-110-18452/27071-5
Keywords: N0; Z1; 330; Inflation Trauma; Hyperinflation; Stability Culture; Monetary History; Collective memory